2014
DOI: 10.1111/mmi.12632
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to the two‐peptide bacteriocin lactococcin G is dependent on UppP, an enzyme involved in cell‐wall synthesis

Abstract: SummaryMost bacterially produced antimicrobial peptides (bacteriocins) are thought to kill target cells by a receptor-mediated mechanism. However, for most bacteriocins the receptor is unknown. For instance, no target receptor has been identified for the two-peptide bacteriocins (class IIb), whose activity requires the combined action of two individual peptides. To identify the receptor for the class IIb bacteriocin lactococcin G, which targets strains of Lactococcus lactis, we generated 12 lactococcin G-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 46 publications
(76 reference statements)
3
73
0
1
Order By: Relevance
“…Types of receptors appear to be targeted by several related and sometimes also nonrelated bacteriocins. For instance, the permease mannose-phosphotransferase (PTS) is targeted by many pediocin-like bacteriocins, in addition to the unrelated lactococcins A and B (48), whereas a zinc-dependent membrane-bound protease belonging to the M50 family is targeted by several related leaderless bacteriocins (49; unpublished results), and the undecaprenyl pyrophosphate phosphatase UppP (a membrane protein involved in peptidoglycan synthesis) is targeted by the two-peptide bacteriocins lactococcin G and enterocin 1071 (50).…”
Section: Antimicrobial Spectrum and Mode Of Actionmentioning
confidence: 99%
“…Types of receptors appear to be targeted by several related and sometimes also nonrelated bacteriocins. For instance, the permease mannose-phosphotransferase (PTS) is targeted by many pediocin-like bacteriocins, in addition to the unrelated lactococcins A and B (48), whereas a zinc-dependent membrane-bound protease belonging to the M50 family is targeted by several related leaderless bacteriocins (49; unpublished results), and the undecaprenyl pyrophosphate phosphatase UppP (a membrane protein involved in peptidoglycan synthesis) is targeted by the two-peptide bacteriocins lactococcin G and enterocin 1071 (50).…”
Section: Antimicrobial Spectrum and Mode Of Actionmentioning
confidence: 99%
“…Lactococcin G consists of two unmodified subunits, LcnG-a (GTWDDIGGGIGRVAYWVGKA MGNMSDVNQASRINRKKKH) and LcnG-b (KKWGWLAWVDPAY EFIKGFGKGAIKEGNKDKWKNI) (Kjos et al, 2014). Both LcnG-a and LcnG-b were commercially synthesized with 90 % purity (Pepmic).…”
mentioning
confidence: 99%
“…Recently, UppP/BacA has been found to be the receptor for lactococcin G and is presumed also to be the receptor for lactococcin Q (Kjos et al, 2014). In addition, the regions including the N-terminal end of lactococcin Ga (residues 1 to 13) and the C-terminal part of lactococcin Gb (residues 14 to 24) were identified as recognition regions by LagC.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kjos et al (2014) showed that the undecaprenylpyrophosphate phosphatase (termed UppP in L. lactis subsp. lactis IL1403 and BacA in L. lactis subsp.…”
Section: Introductionmentioning
confidence: 99%